Genetic variants and carotid atherosclerosis progression in familial hypercholesterolemia: a comprehensive review - Bekbossynova, Makhabbat; Ivanova-Razumova, Tatyana; Azatov, Yerkin; Sailybayeva, Aliya; Khamitov, Sadyk; Daniyarova, Gulnur; Akzholova, Kamila (Frontiers in Cardiovascular Medicine, 2025)
IntroductionFamilial Hypercholesterolemia is a hereditary metabolic disorder characterized by elevated low-density lipoprotein cholesterol, as high as 1 in 250 individuals, leading to cardiovascular diseases like atherosclerosis. It's caused by autosomal dominant mutations in genes LDL receptor, Apolipoprotein B-100, and proprotein convertase subtilisin/kexin type 9 (PCSK9), FH leads to lifelong elevation of LDL-C. Carotid atherosclerosis, a sign of systemic atherosclerosis, can be studied as a clinical feature of FH, providing insights into its risk assessment, early diagnosis, and intervention.ObjectiveTo determine contribution of specific genetic variants to carotid atherosclerosis, thereby improving our understanding of the genetic basis of cardiovascular risk in FH.MethodsA search was performed through PubMed, Google Scholar, Medline and Scopus databases using the preselected terms. Studies were selected and reviewed based on inclusion and exclusion criteria by two authors independently, with third-party adjudication.ResultsTotal of 9 trials were included: 4 cross-sectional studies, 4 retrospective cohorts and 1 prospective cohort studies. Total sample size of all reviewed studies was 3,033 in different settings. Studies revealed higher cIMT levels in FH patients and showed significant association of LDLR mutations with severe atherosclerosis. APOB and PCSK9 mutations in this study had limited effect on cIMT levels and prevalence of carotid plaques.ConclusionThis review highlights the essential role of LDLR mutations in progression of carotid artery atherosclerosis among patients with FH. Incorporating information on FH mutations into risk assessment for atherosclerosis patients can help predict disease progression and cardiovascular outcomes more effectively.